Asymmetric Dynamic Model of Temperature-Dependent Magnetorheological Damper and Application for Semi-active System - Yu, Jianqiang; Dong, Xiaomin; Wang, Xuhong; Pan, Chengwang; Zhou, Yaqin (Frontiers in Materials, 2019)
As semi-active hydraulic device, magnetorheological (MR) damper’s damping characteristics will be influenced by temperature. In addition, the MR damper with gas accumulator usually shows asymmetric loop characteristics. To capture the hysteretic characteristics of MR dampers accurately, a developed model considering the temperature effects and asymmetric characteristics is proposed and analyzed. A typical mono-tube MR damper with gas accumulator is designed and tested under different sinusoidal excitations, currents and temperatures for obtaining the temperature-dependent and asymmetric damping characteristics. Based on experimental results, the proposed asymmetric model and conventional symmetric model are compared. The accurately asymmetric model is identified to calculated coefficients about current and temperature. The MR systems with symmetric model considering temperature effects, asymmetric model independent with temperature and asymmetric model considering temperature effects are simulated and compared under H∞ control strategy. Results show that the proposed model is the best in accuracy and can be used for semi-active control system.